Preferences for the Success of MSMEs in Digital Literacy Using the Conjoin Method - Efendi, Ervin Yanuardi; Maulina, Erna; Kostini, Nenden (International Journal of Science and Society, 2024)
Research exploring how increasing digital literacy can strengthen the competitiveness and growth of MSMEs in digital literacy is discussed in the context of Functional skills Beyond, Creativity, Collaboration, Communication, Cultural and social Understanding Critical Thinking and Evaluation E-Safety, Ability to Find and Select Information. Researchers emphasize the problems faced in increasing digital literacy, such as limited access, incompetence, and the spread of misinformation. The research method uses conjoint analysis, with a sample size of 100 respondents. The sampling carried out in this research was using a nonprobability sampling technique, the collection method was carried out using a purposive sampling method. Data analysis was carried out using IBM SPSS 23. The results of the research show that the utility coefficient value of the attribute of being able to discuss and negotiate other people's opinions is the highest attribute among other attributes with a utility value of 0.313. Attribute Using digital technology in various types and formats with a utility value of 0.213. Attributes Able to understand and understand customers. In accordance with the context of socio-cultural understanding with a utility value of 0.175. Attributes Able to explore, be creative, use digital technology with a utility value of 0.038.